EVALUASI PENYELENGGARAAN VAKSINASI MASSAL YANG DILAKSANAKAN OLEH PEMERINTAH BAGI MAHASISWA STIKES AWAL BROS PEKANBARU - Latisa Shafa Maura Maura; Danil Hulmansyah (Journal of Hospital Administration and Management (JHAM), 2021)
The Covid-19 pandemic is the spread of coronavirus disease 2019 worldwide. The disease is caused by a new type of coronavirus called SARS-CoV-2. The Covid-19 outbreak was first detected in Wuhan City, Hubei, China on December 31, 2019, and was designated a pandemic by the World Health Organization (WHO) on March 11, 2020. Due to the increasing outbreak of Covid-19 today, the government is taking an important strategy, namely by implementing the Covid-19 vaccination program enmasse. The purpose of vaccination is to increase immunity by activating antibodies in the body so as to reduce the impact of Covid-19 transmission which is expected to break the chain of transmission of Covid-19 disease. The purpose of this study is to find out how students assesment of the implementation of mass vaccinations carried out by the government. The method in this study is to use a canoe model to test how the performance of mass vaccination implementation carried out by the government for student STIKes Awal Bros Pekanbaru. Based on the results of data collection, processing and analysis that has been carried out, there are no indicators that must be improved or maintained, because with the condition of the mass vaccination site, visitors still visit the vaccination site and are still satisfied with the quality of the current vaccination implementation. Furthermore, althought there are no must-be indicators, the place of vaccination also needs to make certain improvements and improvements to some indikators, so that the satisfaction of visitors where vaccination is carried out is increasing.